المبدأ التداولي في نظرية اللسانيات النسبية وأثره في تركيب الجملة العربية - ريـال, فتيحة; صالحي, علي (University of Eloued جامعة الوادي, 2024)
يناقش هذا البحث أحدَ أهمِّ المبادئ الكلّية التي تتقوّم بها ماهيّة اللّغة في نظريّة اللّسانيات النسبية، وهو "المبدأ التداولي" الذي يُشكّل دعامة رئيسة لأي نظرية لسانية تنشد بلوغ الكفايتين الوصفية والتفسيرية، فللّغة وظائف تداولية تُجلي الكثير من أبعادها بنية العبارة اللغوية ذاتها، وتلك الوظائف تحكمها العلاقة التخاطبية بين منتج الخطاب ومؤوّله، الأمر الذي يفسّر إدراج المكوّن التداولي في تحديد ماهية اللغة؛ فالوظيفة المحورية لهذه الأخيرة هي التواصل والتبليغ، ما يعني حتمية تأثّر بنيتها بمتطلّبات تحقيق هذه الوظيفة، أي أصول المبدأ التداولي. تأسيسا على ما سبق، ننظر من خلال هذا البحث في أصول تكوّن المبدأ التداولي كما هي ماثلة في الجهاز الواصف لنظرية اللسانيات النسبية، قصد تلمّس أثره في تركيب الجملة العربية. وقد توصّلنا إلى رصد عدد من الظواهر اللغوية التي يتجلّى في مضانها أثر المبدأ التداولي في التركيب، مبرزين من خلالها أهمّية هذا المبدأ في نظرية اللسانيات النسبية. This paper discusses the pragmatic principle which is one of the universal principles underlying the language essence with in the relative linguistics theory. Besides, it is the main basis for any linguistic theory aiming at achieving the interpretive and descriptive competencies. Language has pragmatic functions whose dimensions are shown by the structure of the linguistic expression itself. These functions are governed by the discursive relation between the discourse producer and its recipient/interpreter; which explains the inclusion of the pragmatic component in identifying the essence of language whose pivotal role is communication and information. This means that its structure is inevitably influenced by the requirements of achieving this function, i.e. the origins of the pragmatic principle. Based on the foregoing, this paper investigates the origins of the pragmatic principle as they are in the description of the relative linguistics theory in view to figure out its impact on the Arabic sentence structure. Findings show a set of linguistic phenomena making plain the impact of the pragmatic principle on structure and highlight the importance of this principle within the relative linguistics theory.
the Pragmatic Principle In The Relative Linguistics Theory And Its Impact On The Arabic Sentence Structure
مقال. مجلة القارئ للدراسات الأدبية و النقدية و اللغوية . مج07 . ع.02. جامعة الوادي
Keywords: اللّسانيات النسبيّة; المبدأ التداولي; الإعراب التداولي; الترتيب التداولي; موجّهات الجملة; Relative linguistics; Pragmatic principle; Pragmatic analysis; Pragmatic order; Sentence vectors